Implementasi Sanksi Denda Elektronik Traffic Law Enforcement (E-Tle) - Widyanto Nugroho; Haniyah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Every motorized vehicle driver must comply with traffic rules and regulations. This aims to ensure the safety of motorized vehicle drivers and other road users. But because of the increase in the number of motorized vehicles, the accident rate continues to increase every year and the number of victims continues to increase, which is one of the bad factors in the increase in the number of motorized vehicles in Indonesia. This factor occurs due to the driver's human negligence, starting from lack of sleep, fatigue, carelessness, and low rider discipline. The police enforced it with fines but it was still frequently violated by motorists. Therefore, the existence of electronic tickets (E-TLE) using CCTV surveillance cameras, is expected to help reduce violations and reduce the level of road accidents. This study raises problems by looking at the obstacles experienced in the implementing E-TLE ticket fines and the obstacles experienced in the implementing E-TLE ticket fines in the jurisdiction of the Surabaya City Police. This research uses empirical juridical research. The results of this study are the obstacles that traffic police officers face when applying ETLE fines are: Unclear ETLE cameras, lots of fake license plates, E-tickets that are not on target, Accessibility of the application network, E-ticket services that are just In Time, integration of data that has not been uploaded, lack of socialization and the community does not have the E-Tilang application. And the obstacles faced by traffic police officers when applying ETLE fines are: factors of law enforcers who still accept bribes and lack of understanding of Law Number 22 of 2009 concerning Road Traffic and Transportation, Community factors, namely the lack of understanding of the community in driving on the highway and the lack of knowledge about traffic violations, and application system factors and electronic devices where there are still errors in their use and CCTV cameras that are not clear in photographing violating motorists.